Metamaterials in multilayer graphene photonics: Control of negative refraction. (April 2016) - Da, Haixia; Yan, Xiaohong
Abstract: Negative refraction medium can in principle be realized using artificial composites composed of semiconductor/metallic inclusions, which experience negative refraction over certain frequency region due to structural resonant. It would be desirable if we could extend negative refraction to alternative natural semimetal candidates. Here, we show that by employing multilayer-graphene and cubic boron nitride slab, the composite may support negative group refractive angle over certain frequencies due to its anisotropic characteristics. Poynting vector profile numerically demonstrates that transverse magnetic wave propagates with observable negative shift as if they had negative refractive index.